THE HISTORY OF MODERN ISLAM IN IRAN AND THE REFORM IDEAS OF AYATOLLAH KHOMEINI: Sejarah Islam Modern di Iran dan Ide-Ide Reformasi Ayatollah Khomeini - Muhammad Yunus (Jurnal Diskursus Islam, 2025)
The Safavid Persian Empire is one example of Muslim politics during the early development of Islam. Compared to the other two great empires, the Mughal and Ottoman empires, the Safavid Empire faced the most pressure from the West. As is well known, the progress of a nation depends on its development; the younger generation of Iran achieved progress that enabled them to stand on their own and no longer depend on other countries. Western countries were keen to exert pressure on Iran. This paper aims to study the history of contemporary Islamic development in Iran, from the reform ideas of Ayatollah Khomeini to how they were implemented in the country. To provide the description, the author uses a qualitative historical research approach. The findings show that the growth of Islam in Iran began with Caliph Umar bin Khattab through the expansion of Islamic territories. However, during this period, the Qajar Dynasty (1785–1925 AD) and the Pahlavi Dynasty (1925–1979 AD) did not achieve significant Islamic progress. The Iranian Revolution not only changed the economy but also created a new and independent government.